Genetic Mapping of the Gmpgl3 Mutant Reveals the Function of GmTic110a in Soybean Chloroplast Development - Yu, Hui; Wang, Qiushi; Zhang, Zhirui; Wu, Tao; Yang, Xinjing; Zhu, Xiaobin; Ye, Yongheng; Leng, Jiantian; Yang, Suxin; Feng, Xianzhong (Frontiers in Plant Science, 2022)
The generation of oxygen and organic matter in plants mainly depends on photosynthesis, which directly affects plant growth and development. The chloroplast is the main organelle in which photosynthesis occurs. In this study, a Glycine max pale green leaf 3-1 (Gmpgl3-1) mutant was isolated from the soybean mutagenized population. The Gmpgl3-1 mutant presented with decreased chlorophyll contents, reduced chloroplast stroma thylakoids, reduced yields, and decreased numbers of pods per plant. Bulked segregant analysis (BSA) together with map-based cloning revealed a single-nucleotide nonsynonymous mutation at the 341st 15 nucleotide of the first exon of the chloroplast development related GmTic110a gene. The phenotype of the knockout plants was the same as that of the mutant. The GmTic110a gene was highly expressed in the leaves at various developmental stages, and its protein was localized to the inner chloroplast membrane. Split luciferase complementation assays and coimmunoprecipitation (co-IP) experiments revealed that GmTic110a interacted with GmTic20, GmTic40a and GmTic40b in tobacco leaves. These results indicated that the GmTic110a gene plays an important role in chloroplast development.